Mark’s Son of Man and Paul’s Second of Adam - Kirk, J. R. Daniel (Horizons in biblical theology, 2015)
Both Mark’s son of man Christology and Paul’s second Adam Christology depict Jesus functioning as an idealized human figure. In each, a core component is Jesus’ obedience in going to death on a cross. This, in turn, is a representative obedience that leads to the conquest of hostile powers. Jesus’ death, moreover, becomes a model for the life of his followers within both models. These Christologies also encompass Jesus’ resurrection and heavenly enthronement at God’s right hand, and both interpret this as entailing a restoration of humanity’s primeval vocation to rule the world on God’s behalf. Finally, participation of Jesus’ followers in his eschatological glory underscores that for both Mark and Paul these are high, human Christologies.